Clinical, Surgical and Histopathologic Outcomes of Filipino Patients with Micropapillary Thyroid Carcinoma in a Tertiary University Hospital in the Philippines - Guerrero, Ruby Jane; Lou Malong, Chandy; Caringal, Jean Abigaile; Sio, Cherry; De Villa, Vanessa Grace; Kho, Sjoberg (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Objective. Micropapillary thyroid carcinoma (micro-PTC) has a good prognosis but a number of cases will present with aggressive behavior. This study aims to determine the clinical outcomes with surgical management and histopathologic characteristics of Filipino patients with micro-PTC at University of Santo Tomas Hospital. Methodology. 139 patients were diagnosed with micro-PTC from the year 2004-2011. Seventy five patients had complete data and were included in this retrospective study. Chi square test with Yates correction, T-test for tumor diameter, statistical means and percentages were used in data analysis. Results. A total of 1,689 thyroid surgeries were done between 2004 and 2011. There were 1,054 patients (62.4%) diagnosed with benign thyroid tumor(s) and 635 patients (37.6%) with well-differentiated thyroid carcinoma. Of these, 139 (22%) patients have micro-PTC. The prevalence rate of micro-PTC was 22%, with a female predominance (86.6%). The patients’ ages ranged from 24-80 years old with a mean age of 47 years. Comparison of groups showed that having either incidental or non-incidental micro-PTC is independent of the clinical variables of the patient. Two (2.6%) patients initially presented with cranial and supraclavicular metastasis. This study had a low recurrence rate (5.3%) and a mortality rate of 1.3%. Conclusion. Male gender is the only significant variable for lymph node and distant metastasis. The patient’s age, family history of cancer, number of foci, size and histological type of tumor have no prognostic value.